Chemo-enzymatic synthesis of (R)-(+)-aminoglutethimide by kinetic resolution of (+/-)-4-cyano-4-phenyl-1-hexanol - Im, DS; Cheong, CS; Lee, SH; Jung, YK; Jeong, IH (ELSEVIER SCIENCE BV, 2003)
Chemo-enzymatic approaches for the synthesis of the family of aromatase inhibitory drug via lipase-catalyzed kinetic resolution of (+/-)-4-cyano-4-phenyl-1-hexanol (2) as appropriate precursors were described. Enzymatic transesterification of primary alcohol (+/-)-2 using Pseudomonas cepacia (Amano PS, PCL) provided the enantiopure alcohol (R)-(-)-2 with 99% ee at conversion of 86%, while that of (+/-)-2 using Pseudomonas fluorescens (Amano AK, LAK) provided the (S)-(+)-2 with 96% ee at conversion of 86%. Chemical transformation of substrate (R)-(-)-2 gave (R)-(+)-aminoglutethimide (1) in enantioselectively high yield. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: BENZYLIC QUATERNARY CARBONS; ASYMMETRIC CONSTRUCTION; AROMATASE; ANALOGS; AMINOGLUTETHIMIDE; 3-ETHYL-3-(4-PYRIDYL)PIPERIDINE-2,6-DIONE; DERIVATIVES; INHIBITION